2010
DOI: 10.1037/a0017781
|View full text |Cite
|
Sign up to set email alerts
|

Building the infrastructure: The effects of role identification behaviors on team cognition development and performance.

Abstract: The primary purpose of this study was to extend theory and research regarding the emergence of mental models and transactive memory in teams. Utilizing Kozlowski et al. 's (1999) model of team compilation, we examine the effect of role identification behaviors and argue that such behaviors represent the initial building blocks of team cognition during the role compilation phase of team development. We then hypothesized that team mental models and transactive memory would convey the effects of these behaviors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 60 publications
(117 reference statements)
0
81
0
Order By: Relevance
“…They argue that team size serves as a rough estimate of team member interaction opportunity, but they do not study these interaction and communication processes directly. However, some recent work has proposed theoretical frameworks for the development of team mental models (e.g., Langan-Fox, 2003;McComb, 2008) and empirical studies have started to focus more specifically on the processes that influence the development of mental models (e.g., Pearsall et al, 2010). We believe more work is needed in this area.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They argue that team size serves as a rough estimate of team member interaction opportunity, but they do not study these interaction and communication processes directly. However, some recent work has proposed theoretical frameworks for the development of team mental models (e.g., Langan-Fox, 2003;McComb, 2008) and empirical studies have started to focus more specifically on the processes that influence the development of mental models (e.g., Pearsall et al, 2010). We believe more work is needed in this area.…”
Section: Discussionmentioning
confidence: 99%
“…This exchange may occur through a variety of mechanisms, including informal and social interaction, shared task experiences, and formal interventions. Pearsall, Ellis, and Bell (2010) recently showed that the number of role identification behaviors (e.g., sharing or requesting information about roles) exhibited by a team during the early stages of their development was positively related to the development of teaminteraction mental models. Similarly, Levesque, Wilson, and Wholey (2001) found that as role differentiation increased in software development teams, there was a decline in shared mental models.…”
Section: Team Mental Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, within the context of developing TMSs in multidisciplinary healthcare teams, the goals prioritized by professional subgroup identification complement the goals stemming from team identification. Specifically, both identification processes place emphasis on capturing the diversity of professional expertise in the team in the delivery of patient care, and moreover, in building a TMS infrastructure (of where specialized knowledge is to be assigned, processed, and retrieved from), the focus also is on identifying the professional roles occupied in the team (Pearsall et al, 2010). Furthermore, Heckman and colleague examined organisational identification and professional identification on organisational effectiveness outcomes.…”
Section: Theoretical Implicationsmentioning
confidence: 99%